Barriers and facilitators to mental health promotion for Mexican immigrants in the U.S. through the Ventanillas de Salud program - González Casanova, Inés; Martínez Rodriguez, Delia Lilian; Ortiz Brunel, Julissa; Rangel Gómez, María Gudelia; de Groot, Mary; Fernández, Alicia (Frontiers in Public Health, 2023)
Abstract Introduction: Mental health promotion and screenings are recommended as part of standard preventive care. Mexican immigrants in the U.S. are at high risk for mental health illness especially after the COVID-19 pandemic, however access to mental health prevention for this population has been limited, which results in important implementation and equity gaps. The Ventanilla de Salud (VDS) program provides preventive services through Mexican consulates in the U.S. Objective: The objective of this study was to assess capability, opportunity, and motivation for promotores to implement mental health programming through the VDS, leveraging early experiences of ongoing mental health prevention efforts. Methods: This was a qualitative study using the Capability, Opportunity, and Motivation for Behavior Change model (COM-B). We conducted 9 focus groups with 40 VDS promotores and 6 semi-structured interviews with program stakeholders. Data were analyzed using inductive and deductive coding. Results: We found high levels of interest from the leadership, partners, and promotores to provide mental health services through the VDS. Early implementation of a mental health strategy that included training sessions for promotores and mental health promotion, screenings and referrals for VDS users was ongoing. We identified facilitators and barriers that could affect capability, opportunity, and motivation to provide mental health services. Facilitators included promotores’ extensive knowledge about the importance of mental health, promotores service mindset and commitment to provide services to VDS users, and general support from the VDS network and partners. Barriers included promotores’ turnover, need for additional economic compensation, burnout, competing priorities, and lack of mental health professionals to provide clinical services or supervision. Additional investments are recommended to support promotores’ well-being. Conclusion: The main lesson learned from this study was that investing in VDS promotores’ training, resources, and well-being is key to their capability, opportunity and motivation to provide mental health services for Mexican immigrants in the US. Results from this study can be applied to improve the ongoing VDS mental health strategy and increase its impact on the mental health of Mexican immigrants.